1998
DOI: 10.1111/j.1095-8649.1998.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Spanish barbel species using the RAPD technique

Abstract: The RAPD-PCR technique was employed to identify three endemic Spanish species of Barbus: Barbus bocagei, B. graellsii and B. sclateri, that present very similar morphologies. Using seven primers, six diagnostic bands were found in B. bocagei, 11 in B. graellsii and nine in B. sclateri. Cluster analysis of the genetic similarity values obtained from RAPD data indicated that the species B. bocagei and B. graellsii are more related to each other than to B. sclateri. 1998 The Fisheries Society of the British Isles Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…RAPD markers are efficient in species discrimination, particularly in cases where morphologic characteristics have low resolving power (Callejas and Ochando, 1998). Besides the classical application on estimates of genetic similarity among populations, RAPD markers have been used successfully to determine species-specific traits in fishes (Dinesh et al, 1993;Takagi and Taniguchi, 1995;Callejas and Ochando, 1998) and for reconstructing phylogenetic relations among species and subspecies (Bardakci and Skibinski, 1994;Callejas and Ochando, 1998). Since heterozigotes are not separated from homozigotes due to the dominant character from the RAPD markers, the absence of amplification of a band in two genotypes does not necessarily represent genetic similarity between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAPD markers are efficient in species discrimination, particularly in cases where morphologic characteristics have low resolving power (Callejas and Ochando, 1998). Besides the classical application on estimates of genetic similarity among populations, RAPD markers have been used successfully to determine species-specific traits in fishes (Dinesh et al, 1993;Takagi and Taniguchi, 1995;Callejas and Ochando, 1998) and for reconstructing phylogenetic relations among species and subspecies (Bardakci and Skibinski, 1994;Callejas and Ochando, 1998). Since heterozigotes are not separated from homozigotes due to the dominant character from the RAPD markers, the absence of amplification of a band in two genotypes does not necessarily represent genetic similarity between them.…”
Section: Discussionmentioning
confidence: 99%
“…Informations derived from molecular genetic techniques shall contribute significantly for the preservation of aquatic genetic resources and sustainable development (Carvalho, 1993;Chiari, 1999;Martins et al, 2003;Almeida et al, 2003). The RAPD procedure (Randomly Amplified Polymorphic DNA) has been instrumental to understand the genetic variability of fish populations (Bielawski and Pumo, 1997;Caccone et al, 1997;Callejas and Ochando, 1998;Dergam et al, 1998;Nadig et al, 1998;Liu et al, 1999;Prioli et al, 2002;Shikano and Taniguchi, 2002;Almeida et al, 2003;Bártfai et al, 2003;Hatanaka and Galetti Jr, 2003). This technique consists of amplification by PCR (Polymerase Chain Reaction) of random segments of genomic DNA using a single short primer of arbitrary sequence.…”
Section: Introductionmentioning
confidence: 99%
“…There is now increasing evidence that the RAPD technique, which has been used in different fields, can detect nuclear variation in fish (Borowski et al, 1995;Naish et al, 1995;Sultmann et al, 1995;Bielawski and Pumo, 1997;Caccone et al, 1997;Callejas and Ochando, 1998;Mamuris et al, 1999;Allendorf and Seeb, 2000). These studies have shown that RAPD is an extremely sensitive method for detecting DNA variation and for establishing genetic relationships in closely related organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Date first introduction suggests it will worsen and therefore these activities should be avoided, to safeguard fish species fauna [66][67][68][69][70][71][72][73][74][75].…”
Section: Speciesmentioning
confidence: 99%